1990
DOI: 10.1063/1.104138
|View full text |Cite
|
Sign up to set email alerts
|

Application of a near coincidence site lattice theory to the orientations of YBa2Cu3O7−x grains on (001) MgO substrates

Abstract: Various orientations of YBa2Cu3O7−x grains in polycrystalline films prepared on (001)MgO substrates by in situ laser deposition were determined using electron diffraction. Eight different types of in-plane orientations have been observed. These orientations agree well with the prediction of a simplified theory of near coincidence site lattice between YBa2Cu3O7−x and MgO. The YBa2Cu3O7−x grains were found to have a high probability of forming low angle or low Σ boundaries among themselves. These grain boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Earlier, it was reported that the values of d~ in bicrystal-thin-films of YBa2CuaOT_, increase with a decrease in the misorientation angle of the grain boundary [1,2]. However, it was demonstrated later that some large-angle grain boundaries in bicrystals and in thin films transport high currents [3][4][5]. Since very many of the important future applications of the bulk materials inevitably in-*Present address: REM Electron Power Inc., 221 West Industry Court, Deer Park, NY 11729. volve polycrystals, it seems imperative to have an understanding of the structural features of grain boundaries that determine their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, it was reported that the values of d~ in bicrystal-thin-films of YBa2CuaOT_, increase with a decrease in the misorientation angle of the grain boundary [1,2]. However, it was demonstrated later that some large-angle grain boundaries in bicrystals and in thin films transport high currents [3][4][5]. Since very many of the important future applications of the bulk materials inevitably in-*Present address: REM Electron Power Inc., 221 West Industry Court, Deer Park, NY 11729. volve polycrystals, it seems imperative to have an understanding of the structural features of grain boundaries that determine their properties.…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to the lower deposition temperature involved in the nucleation of a-axis grains compared with c-axis grains [5], which leads to films with a generally lower critical transition temperature and poorer crystallinity [6]. While (110) NdGaO 3 substrates [7] have been successfully employed to grow a-axis films, the most reproducible results have been obtained by using a buffer layer technique.…”
Section: Introductionmentioning
confidence: 93%
“…It was reported that the values of J~ in thin films of Y123 are quite sensitive to the misorientation between the adjacent grains and decrease drastically if the misorientation angle exceeds 10 ~ [12][13][14]. However, it was demonstrated recently that in polycrystaUine thin films (with a- (-b), and e-axis oriented grains) [15,16] and bulk bicrystals [17,18] of Y123, some large-angle (90~ GBs transport high currents. Thus the properties of the grain boundaries might be affected by both the atomic structure and chemical composition.…”
Section: Introductionmentioning
confidence: 99%